(untitled) (Revista Española de Estudios Agrosociales y Pesqueros, 2025)
This article addresses the legal consequences of the trade war between the US and the EU, in a context marked by protectionism and tariff instability. The objective is to propose, from International Trade Law and Private International Law, a selection of instruments that can contribute to cushioning the impact of tariffs on this sector. For this reason, general solutions are proposed – not designed for each subsector – considered especially effective: inclusion of contractual clauses (force majeure, applicable law, adaptation mechanisms), internationalisation strategies such as nearshoring, contractual figures such as joint ventures, etc.